Unrecognized schizophrenia spectrum and other mental disorders in youth disconnected from education and work-life - Line Lindhardt; Lars Siersbæk Nilsson; Povl Munk-Jørgensen; Ole Steen Mortensen; Ole Steen Mortensen; Erik Simonsen; Erik Simonsen; Julie Nordgaard; Julie Nordgaard (Frontiers in Psychiatry, 2022)
BackgroundSchizophrenia spectrum disorders typically emerge during adolescence or early adulthood. Often the symptomatology is vague initially, while a marked functional decline and social withdrawal can be seen. A group of young people with such social and functional impairments is the so-called “Not in Education, Employment or Training” (NEET), i.e., a youth population that is socially disconnected from education and work-life. Despite the NEET group’s disconnection from important parts of social life and a rising concern of an intersection with mental health problems, a psychopathological perspective on the problems experienced by this group remains underexplored.AimTo examine a NEET sample for psychopathology and if relevant allocate psychiatric diagnoses.MethodsWe performed an interview study comprising 40 participants from youth job-counseling services. All underwent a comprehensive psychiatric evaluation. Inclusion criteria were 18–29 years of age and a welfare benefit history of minimum 6 months.ResultsDiagnostic criteria of any mental disorder were fulfilled by 95% of the sample; half of whom were diagnosed with a schizophrenia spectrum disorder. The participants with schizophrenia spectrum disorders had lower global functioning, were more often in contact with the mental health services and had higher PANSS and Examination of Anomalous Self-Experiences (EASE) scores compared to those with non-schizophrenia spectrum disorders. The participants fulfilling the criteria for schizophrenia spectrum disorders had lower EASE and PANSS scores than usually reported in the literature, suggesting more “symptom-poor” presentations.ConclusionPsychiatric illness and particularly schizophrenia spectrum disorders affecting social interaction and the ability to take part in educational and work-life were grossly overrepresented in the NEET sample. Our findings suggest that pronounced social disconnection in youth in and of itself should lead to suspect the presence of a severe mental disorder.